Implementasi Algoritma Approximate String Matching Pada Aplikasi Pengarsipan Dokumen Ekspor Barang - Annisa Sihotang, Yola (Buletin Ilmiah Informatika Teknologi, 2024)
This thesis proposal raises the title "Implemetation of Approximate String Matching Algorithm in Export Document Filing Application (Case Study: PT. Chitra Kalpika Mas Kab.Deli Serdang". This proposal is made based on observations made at PT. Chitra Kalpika Mas by looking at the filing system. Export documents are still done manually, the author makes a new system design to improve the old system.The problems studied in this study are how to search for export document archives and the obstacles faced by PT. Chitra Kalpika Mas. And what obstacles have been taken to overcome the existing obstacles. Therefore, we need an application program that can help employees complete their tasks to make it easier, one of which is to search for export document archive data.Based on the research results, it can be concluded that the search for export document archives at PT. Chitra Kalpika Mas is still done manually. Therefore, it is necessary to design a new application using a computer program in accordance with the needs of office employees so that use is easier to obtain quickly and accurately. With the design of an export document archive application, it can facilitate report processing, additions, changes, and deletions of data and can provide information whenever needed